THE CONCEPT OF GASSĀN HAMDŪN ON HIS KITAB TAFSĪR MIN NASAMĀT AL-QUR’ĀN KALIMĀT WA BAYĀN - Hadrawi Abdullah (JICSA : Journal of Islamic Civilization in Southeast Asian, 2019)
The purpose of this study is to find out Gassan Hamdun's concept in the book of Interpretation of the Qur'an of the Qur'an Sentence, the interpretation techniques, the systematic writing and its characteristics, the advantages and disadvantages of the book. The results of this study show that Gassan Hamdun used the Ijmali method in interpreting the verses of the Qur'an which are interpretations based on bi al-ma'sur interpretive books as well as other major interpretive books, namely those of the interpretation books scholars and scholars acknowledge the depth of knowledge of the authors of such books, such as Tafsir Jalalain in interpreting the verse of the Qur'an, the Interpretation of Imam Nasafi in interpreting the Qur'anic verse, Al-Alusi's Interpretation in explaining the sentence in the Qur'an and sometimes also interpret the verses and take the appropriate hadiths and al-nuzul asbab a verse, take the interpretation of al-nuzul verses and asbab al-nuzul a verse in the Ibn Katsir interpretation, taking reference to the knowledge Shariah and its branches in the book "Al-Jami 'Li Ahkam al-Qur'an" by Imam Qurtubi, and to refer to art that can stir the soul and revive the heart in the book of interpretation "Fi Zilal al-Q meaning "the work of Sayyid Qutub. According to Gassan Hamdun the source of the interpretation of bi al-ma'sur is more accurate than the other sources, although he also makes the book of bi al-ra'yi al mahmud interpretations, which are interpretations that rely on ijtihad as a source of interpretation, such as al -Allusion. Gassan Hamdun features a book of interpretations in which each interpretation uses a specific formula and code. The formulas and code are the initials of the letter intended to make it easier for the reader to understand the interpretation of the text, as well as to save the writing in the book, resulting in a beautifully read book.